Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1177/14713012211004009
|View full text |Cite
|
Sign up to set email alerts
|

Mouvement de passage: Creating connections through movement among persons with dementia

Abstract: One of the challenging consequences of dementia is the change in relationships that can co-occur with the progression of this condition. Despite this well-documented change, few arts-based interventions target the relational dimension of dementia. This study aims to explore the effects of one arts-based relational intervention: a movement program designed to foster connections within a group of persons with dementia. We used ethnographic methods—including participant observations and informal interviews—to und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 87 publications
0
7
0
Order By: Relevance
“…Each exercise was accompanied by live music played by the musician using three instruments (kalimba, carillon, Indigenous drum) to structure the pace of the movements. For further description of the session, the reader is referred to (Motta-Ochoa et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…Each exercise was accompanied by live music played by the musician using three instruments (kalimba, carillon, Indigenous drum) to structure the pace of the movements. For further description of the session, the reader is referred to (Motta-Ochoa et al, 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…These characteristics support the use of dancing methodologies as a potentially powerful treatment in the management of neurodegenerative disease. Increasing evidence also suggests that dance interventions/ therapy can improve cognitive function, reduce agitation and aggression, and other difficult individual specific dementia-related issues (Motta-Ochoa et al 2021). In addition, dance also provides potentially isolated individuals with the ability to form relationships, to socially interact with others and to improve their quality of life and societal meaningfulness.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, dance also provides potentially isolated individuals with the ability to form relationships, to socially interact with others and to improve their quality of life and societal meaningfulness. Research has also demonstrated that dance interventions increase the quantity and quality of social interactions and individual connections experienced by participants with dementia (Motta-Ochoa et al 2021). Additionally, dance provides participants with mechanisms to examine new movement patterns providing connections with like-minded individuals and with themselves (Motta-Ochoa et al 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations